Higher Visual Function Deficits in Children With Cerebral Visual Impairment and Good Visual Acuity - Chandna, Arvind; Ghahghaei, Saeideh; Foster, Susan; Kumar, Ram (Frontiers in Human Neuroscience, 2021)
In clinical practice Cerebral Visual Impairment (CVI) is typically diagnosed by observation of abnormal visually-guided behaviors which indicate higher visual function deficits (HVFDs) suggesting abnormal brain development or brain damage in a child with a suitable clinical history. HVFDs can occur even in the presence of good visual acuity and may remain undiagnosed because the good visual acuity does not prompt further investigation. This leads to a lack of understanding of the child’s visual perceptual difficulties. In a prospective study, we determined the spectrum of HVFDs in a group of children with history suggestive of brain damage or disruption of brain development and an independent diagnosis of CVI in comparison with typically developing children with a structured 51 question inventory, the Higher Visual Function Question Inventory (HVFQI-51) adapted from the Cerebral Vision Impairment Inventory, CVI-I (1, 2). Here, we show that the HVFQI-51 can detect a range of HVFDs in children with CVI with good visual acuity and clearly distinguishes these children from typically developing children. HVFDs in our study group could mostly be attributed to dorsal stream visual processing dysfunction though the spectrum varied between children. We report on the inclusion of the ‘not applicable’ response option in analysis providing a picture of HVFDs more in tune with the overall disability of each child. We also propose a subset of 11 questions (Top-11) which discriminate between children with CVI versus behaviors seen in typical children: this provides both a potential screening tool for initial assessment of HVFDs and a measure of CVI-related impairment, need further validation in a secondary independent sample.